2017
DOI: 10.1038/cddis.2017.369
|View full text |Cite
|
Sign up to set email alerts
|

PDI is an essential redox-sensitive activator of PERK during the unfolded protein response (UPR)

Abstract: Endoplasmic reticulum (ER) stress leads to activation of the unfolded protein response (UPR) that results in transient suppression of protein translation to allow recovery but leads to cell death when stress cannot be resolved. Central to initiation of the UPR is the activation of the ER transmembrane kinase protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK). Here we report that the thiol oxidoreductase ERp57 and protein disulfide isomerase-A1 (PDI), which belong to the same family of luminal ER o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 44 publications
0
75
0
Order By: Relevance
“…Similarly, components of IRE1 and PERK signaling pathways may also bind to the GRP78 promoter to elevate GRP78 transcription 46,47 . The roles of PDI in the regulation of ER stress sensor proteins are not well understood, however, PDI is an essential redox-sensitive activator of PERK 48 . In unstressed condition, ERp57 keeps PDI in a reduced state.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, components of IRE1 and PERK signaling pathways may also bind to the GRP78 promoter to elevate GRP78 transcription 46,47 . The roles of PDI in the regulation of ER stress sensor proteins are not well understood, however, PDI is an essential redox-sensitive activator of PERK 48 . In unstressed condition, ERp57 keeps PDI in a reduced state.…”
Section: Discussionmentioning
confidence: 99%
“…7C, alteration of intracellular redox state in FaO cells resulted associated to a progressive and persistent increased expression of PDI family involved in UPR triggering. Among PDI proteins, we found a progressive increase in PDI and ERp72 protein expression, and a decrease of ERp57 and calnexin 43 protein expression except for an unexpected increase at 42 and 30 hours, respectively. α-LA induces ER stress in HepG2 cells through upregulation of UPR.…”
Section: α-La-treated Fao Cells Show Dysregulation Of Genes Involved mentioning
confidence: 72%
“…PDIs are known to be responsible for the oxidation (formation), reduction (break down) and isomerization (rearrangement) of protein disulfide bonds via disulfide interchange activity. The other major role of PDIs is in general chaperone activity and recent studies have also identified PDI for its role as PERK activator (50–52). In Figure 2, it is interesting to observe that mRNA-level upregulation is countered by protein-level down-regulation of DnaJ heat shock protein family (Hsp40) member C3 (DNAJC3), which is a known inhibitor of PERK (53).…”
Section: Resultsmentioning
confidence: 99%